Molecular docking study and mapping the binding site of some antiviral nanobodies against receptor binding domain (RBD) of SARS-COV 2 - zahra pahlavan; Mohammad Hossein Fatemi (Nanochemistry Research, 2021)
Neutralization ability of some antiviral nanobodies was computed against the receptor binding domain (RBD) of the severe acute respiratory syndrome coronavirus 2 (SARS-COV 2). CoDockPP Server and COVID-19 Docking Server respectively was applied for a protein-protein molecular docking. The affinity of candidate nonobodies was investigated for blocking of RBD against the human angiotensin coverting enzyme 2 (ACE2). The neutralization ability of nonobodies was compared with natural nanobodies of Ty1, H11-H4, EY6A, H11-D4 and synthetic construct of Sb23, ybody MR17, sybody MR17-K99Y, and SR4 that experimentally was involved against the RBD of SARS-COV 2. It was seen, the 15 reported VHH was able for blocking with an estimated binding energy greater than -235.55 (kcal/mol) for Ty1 with the lowest affinity to the RBD. VHH 7A, VHH PVSP29F, Cameld VHH 9, VHH PVSS8A, VHH 12B, VHH 59H10, VHH PVSP6A, VHH 10E, VHH 17B and VHH 59H10 respectively was proposed for neutralization of RBD while the two last VHH are more confidence due to the greater values of affinity against -342.56 (kcal/mol) for SR4. The energy maps of ACE2, VHH 17B and VHH 59H10 was identified that hydrogen donor, steric, hydrogen acceptor and electrostatic interactions respectively were significant for blocking RBD of SARS-COV 2. This study conform structural insight for neutralization of RBD spike glycoprotein of SARS-COV 2 by nanobodies and suggest VHH that may serve as useful therapeutics during the pandemic.